Primary synovial sarcoma of lung - Devleena (Lung India, 2014)
A synovial sarcoma (SS) is a rare form of cancer which usually occurs near the joints of the arm, neck, or leg, but has been documented in most human tissues and organs, including the brain, prostate, and heart. Primary pulmonary SS is an extremely rare tumor. We report a case of primary SS of lung who presented with severe chest pain and a large right lung mass with right-sided pleural effusion in computed tomography (CT) scan of thorax. The diagnosis was made on the basis of CT-guided core biopsy and immunohistochemistry. On immunohistochemistry, tumor cell expressed epithelial membrane antigen, bcl 2, Vimentin and smooth muscle actin and were immunonegative for S100 and cytokeratin. So, the final diagnosis was primary SS.